The impact of vitamin D on breast cancer treatment: literature review - Fedosenko, Mariia (Archive of Oncology, 2024)
Background: Despite the progress in individualizing breast cancer therapy and achieving success in surgical and systemic treatment, the mortality remains high, which requires the search for new targets that can have a significant direct or indirect contribution to the development and prognosis of this disease. One such factor is vitamin D, which is deficient in most parts of the world, and its serum and receptor status have been extensively studied. Numerous studies have been published on the protective effects of vitamin D on breast cancer and other malignancies, risk of development, and treatment outcomes, in particular, increasing the sensitivity of tumors to systemic therapy, survival, and prognosis. Methods: The authors analyzed and systematized research data on the predictive effect of vitamin D on the prognosis and course of breast cancer, the manifestation of its “non-classical” effects in preclinical and clinical studies, and assessed the possible practical application of the results obtained at the molecular-cellular level. The results allow us to use vitamin D as an important marker for monitoring the skeletal system’s state during and after breast cancer treatment. In addition, vitamin D and its analogues in combination with other cytostatic drugs can help search for possible new therapeutic targets. Conclusion: The presented results of vitamin D activity associated with the stages of carcinogenesis undoubtedly open up prospects for finding new possibilities for the treatment and prevention of breast cancer, creating prospects for further research to improve the prognosis and survival rates for such patients. The studied cytotoxic effects expand the field of clinical research on the “non-classical” properties of vitamin D and allow the integration of data on a potential antitumor agent for many malignant tumors.